Cryptic Invasion by Capsella Rubella in Chile Detected by Arms-Pcr - Castro-Morales, S (CSIRO, 2014)
Cryptic species are morphologically similar species that tend to be recognised as a single taxon. The genus Capsella contains two cryptic species, C. bursa-pastoris and C. rubella, which are sympatrically distributed on the Iberian Peninsula, but only one of them (C. bursa-pastoris) has been recognised as an introduced species in South America. In continental Chile, two specimens of C. rubella were collected from two distant sites, but it is unclear whether this indicates only local presence or a wider distribution. After extensive sampling throughout continental Chile, we analysed the diversity of collected Capsella specimens using molecular markers. Our aim was to establish the presence of C. bursa-pastoris and/or C. rubella in continental Chile. To this end, we used an amplification refractory mutation system (ARMS) to detect the trnD-trnY fragment of cpDNA, which allowed the differential amplification of polymorphic sites for both species. A subsample of these amplification products (n?8 fragments) was sequenced and compared with previously documented sequences for C. bursa-pastoris and C. rubella. Of 188 plants, 96.8% were identified as C. bursa-pastoris and 3.2% as C. rubella. C. bursa-pastoris was collected at all localities (28°34S-53°09S), whereas C. rubella was collected only in central-south Chile (34°59S-41°28S). This confirms that both C. bursa-pastoris and C. rubella are present in continental Chile, although they apparently exhibit different abundances and ranges. Our results suggest efforts to elucidate distribution of both Capsella species in South America. © 2014 CSIRO.
Keywords: colonisation; cryptic species; geographic range